Secondary sexual characteristics development pattern in elementary school male students in the municipality of Yogyakarta - Daniel Susatyo Wirawan, Daniel Susatyo Wirawan (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2002)
Background: Twenty two point two percent of Indonesian population are adolescents, and 50.9% of them are male. The development characteristics during puberty are growth spurt, sexual maturation, and secondary sexual development, and these characteristics are affected by nutritional status, health care and social economic status.Objectives: The aim of this study was to investigate the correlation between nutritional status and social factors with the development of secondary sexual characteristics, sexual maturation, and the average age of spermache in YogyakartaDesign: Cross sectional studyMaterial and Methods: One thousand two hundred and sixty three male students enrolled using a proportional population multi stage random sampling were included in this study from all elementary school students in the Municipality of Yogyakarta. Nutritional status was assessed by z-score for weight for age, height for age, and body mass index (BMI). The age of spermache, secondary sexual characteristics, and social factors was obtained by standard questionnaires.Result: Based on z-score value, most of the subjects were wellnourished (84.3%), and normal height (85.3%). Based on BMI most of the students were wasted (62.8%). The average age of spermache in wellnourished, and normal height students were younger than those undernourished, and this difference was statistically significant (p < .001). There was no statistically difference in the development of secondary sexual characteristics between wellnourished and undernourished students, either based on z-score or BMI. Most of the subjects who were exposed to pornography, either pictures (OR 2.20 95% CI 1.31-3.69) or videos (OR 2.09 95%Cl 1.29-3.38) had more spermache than those without experienced. Most of the students (71.74%) were in level 1 of sexual maturity rating (SMR1) based on Tanner scale. There was a relationship between nutritional status based on BMI and sexual maturity rating (p= .007). Conclusions: Nutritional status influenced spermache, and earlier age of spermache, also sexual maturity. Pornography exposure affected spermache.Key words: male students - secondary sexual characteristics - spermache - nutritional status - pornography